FV 7 High-frequency anterior thalamus stimulation increases alertness in epilepsy patients during alert- and drowsy-wakefulness. Issue 10 (October 2017) - Bucurenciu, I.; Staack, A.M.; Gharabaghi, A.; Steinhoff, B.
Abstract : Objective: Deep brain stimulation (DBS) of anterior thalamic nuclei (ANT) reduces frequency and intensity of epileptic partial and secondarily-generalized seizures. ANT-DBS disrupts sleep in epilepsy patients. We investigated the impact of ANT-DBS on alertness in wakeful epilepsy patients. This might help to better understand mechanisms of action of high frequency ANT-DBS in humans. Methods: Four patients with different structural epileptic pathology were included in this retrospective case-cohort study. We analysed physiological parameters of alertness during stimulation-ON and -OFF intervals in short- and long-term electroencephalograms (EEG) of patients in states of alert- and drowsy-wakefulness. Results: We demonstrate that ANT-DBS increases acutely and reproducible the alertness of wakeful patients during stimulation-ON intervals. Significance: This is the first demonstration of such an effect in humans. The enhanced alertness might contribute to the antiepileptic effect of ANT-DBS. Corroborated with the sleep-disruption effect of ANT-DBS in epilepsy patients, our results deliver circumstantial evidences that high-frequency ANT-DBS activates thalamo-cortical connections that promote wakefulness. In addition, our data suggest that ANT-DBS might improve the post-ictal recovery of epileptic patients and counterbalance the antiepileptic-drug induced fatigue.